Analyze slimming tea product using laser induced breakdown spectroscopy - Bidin, Noriah (2012)
Laser Induced Breakdown Spectroscopy (LIBS) is a rapid chemical analysis technology that uses a short laser pulse to create a micro-plasma on the sample surface.